Identifikasi Kandungan Formalin Identification Of Formalin,Borax,and Rhodamine-B In content in fish balls,tofu,and ground chili at Pasar Antri Cimahi City - Juliana, Wanda; Nur Fadilah, Ariska; Ramadhan, Muhammad; Arlianur Mahyaningsih, Manda; Puspa Kania, Adinda; Shinta Permatasari, Dewi; Putri Carissa, Respati; Yusril Firmansyah, Ziyan (JURNAL KESEHATAN KARTIKA, 2023)
Along with the intense competition between manufacturers, food additives used by producers to increase their selling power and attract consumers are no longer limited to natural or synthetic (artificial) additives. In recent years, the abuse of hazardous chemicals as additives for food products has begun to occur. Attractive food colors, chewy food texture, durable food, and affordable prices are things that are considered capable of attracting consumers. The purpose of this study was to identify the presence of borax, formalin, as well as rhodamine-B in fish balls, tofu, and ground chilies at the Cimahi Antri Market. This research method was conducted using a qualitative test. Of the 5 samples, the results showed that 5 samples of ground chili were negative for rhodamine-B, 5 samples of tofu were found to be 3 samples positive for formalin, 5 samples of fish balls showed negative borax. So it can be concluded that 5 samples of ground chili showed negative results for rhodamin-B, 5 samples of fish meatballs showed negative results for borax, and 5 samples of tofu showed 3 positive formalin with sample codes: sample 1, sample 4 and sample 5, while 2 other samples were negative formalin.